Beckman 947A Lead Terminator - Platon-Athan Studios
This instrument was designed to be incorporated into electroencephalograph units and included an impedance meter. An electroencephalogram test detects electrical impulses in the brain via electrodes attached to the scalp.
Keywords: Scientific apparatus and instruments; Electroencephalography; Medical electronics; Beckman Instruments, Inc.